Ser ou Substância (Ousía) - Vella, John (Virtualia Journal, 2013)
Tradução de VELLA, John . “Being or Substance”. Aristotle: A Guide For The Perplexed. London, New York: Bloomsbury Academic, 2008 (p. 26-54)